Do Monetary Incentives Policy Drive EV Adoption? Evidence from Jakarta and Bangkok - Andi Muhammad Sadat; Solikhah Solikhah; Agung Kresnamurti Rivai Prabumenang; Kattareeya Prompreing (AIBPM Publisher, 2026)
This study investigates the factors influencing consumers' intention to buy electric vehicles in Jakarta and Bangkok. It examines the impact of price value, driving range, charging station availability, and monetary incentive policies on purchase intention. The research employs a quantitative technique, which data was collected through an online survey using convenience sampling, targeting individuals aged 17 and above with knowledge and experience related to electric vehicles. The sample consists of 302 respondents, with 167 from Jakarta and 135 from Bangkok. Structural Equation Modeling (SEM) with Partial Least Square (PLS) is used for hypothesis testing. The results reveal that price value, driving range, and charging station availability significantly affect the intention to purchase electric vehicles, while monetary incentive policies do not show a significant impact in both cities. The moderating role of monetary incentive policy on the relationship between price value and purchase intention is also not supported in both cities. The findings provide valuable insights for manufacturers and policymakers in promoting electric vehicle adoption. Future studies could explore additional factors and cover a wider population to guide decision-makers in implementing appropriate adoption of electric vehicles.